Old mosques of the coasts of Abu Dhabi =/ (3GdeSGLO GdbOjeI aj ShGMd CHh XHjs - King, G. R. D. (Abu Dhabi National Archives, 2009)
Published in English and Arabic in a combined volume, this book surveys the various types of traditional mosques on the coast and islands of the Emirate of Abu Dhabi. The study offers a wealth of information about traditional Islamic architecture and structures ranging from basic stone outline mosques representing the simplest form to larger, costlier and architecturally more complex ones built by a society heavily dependent on the sea for fishing, pearling and trade. More importantly, these mosques bear witness to the religiosity of the people, their devout adherence to Islam and their observation of the obligation of prayer. Illustrated with drawings of ground-plans and beautiful pictures taken before and after restoration, of old mosques with inscribed decorations, interior prayer-halls, mihrabs and minbars, wells and hammams, this unique study constitutes an invaluable visual record of the older traditional style of mosques in Abu Dhabi. Particularly useful to researchers are the lists of old mosques known to have formerly existed in Abu Dhabi which have been included in the appendix of the book
Keywords: Mosques--United Arab Emirates--Abu Dhabi (Emirate); (3GdeSGLO(B--(3GdEeGQGJ GdYQHjI GdeJMOI(B--(3CHh XHj (B((3EeGQI(B)s